2022
DOI: 10.3390/ma15041300
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of SiO2 Etch Characteristics by C6F6/Ar/O2 Plasmas Generated Using Inductively Coupled Plasma and Capacitively Coupled Plasma

Abstract: The etching properties of C6F6/Ar/O2 in both an inductively coupled plasma (ICP) system and a capacitively coupled plasma (CCP) system were evaluated to investigate the effects of high C/F ratio of perfluorocarbon (PFC) gas on the etch characteristics of SiO2. When the SiO2 masked with ACL was etched with C6F6, for the CCP system, even though the etch selectivity was very high (20 ~ infinite), due to the heavy-ion bombardment possibly caused by the less dissociated high-mass ions from C6F6, tapered SiO2 etch p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Meanwhile, O radicals formed in plasma are known to play a role in removing the CF x polymer layer. [4] As expected in Figure 5, as the C 6 F 12 O gas ratio increased, the density of the O radical seems to be increased. This indicates that there is a possibility of worsening etch selectivity with the ACL material.…”
Section: Experimental Setup and Proceduressupporting
confidence: 71%
See 2 more Smart Citations
“…Meanwhile, O radicals formed in plasma are known to play a role in removing the CF x polymer layer. [4] As expected in Figure 5, as the C 6 F 12 O gas ratio increased, the density of the O radical seems to be increased. This indicates that there is a possibility of worsening etch selectivity with the ACL material.…”
Section: Experimental Setup and Proceduressupporting
confidence: 71%
“…Considering the fact that all HAR oxide etching processes have been performed with the RIE system and that the HAR oxide etching process cannot be successfully performed with the ICP system, the vertical etched profile extracted using the ICP system is notable. [4,[18][19][20] The vertical etched profiles of SiO 2 dielectrics confirm that HAR oxide etching processes can be performed in ICP etch systems using C 6 F 12 O liquid gas chemistry. Meanwhile, a slight necking phenomenon is observed in Figure 1c, compared with Figure 1d, which exhibits almost no necking.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, most previous studies, especially in the computational area, have focused only on the problems induced by vertical scaling technology, not lateral scaling, especially in the HARC etching process. 8,9,[12][13][14][15] In this article, we address cell density-dependent feature-to-feature variation and distortion induced by lateral scaling, i.e., more holes between slots, during the HARC etching process for the first time. Moreover, the effects of heavy inert ions that incident into the feature of unpreferred etching profiles are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) In addition, to improve the selectivity and etch rate, research on etching using various FC gases with different compositions and structures such as CF 4 , C 2 F 6 , C 2 F 4 , C 3 F 6 , C 4 F 6 , C 4 F 8 , C 5 F 8 , and C 6 F 6 has been conducted. [6][7][8][9][10][11] In the RIE process with FC gas, a suitable thickness of amorphous-CF x (a-CF x ) film deposited on the mask or sidewalls of the hole by CF x radicals plays an important role in protecting the structures from ion bombardment, leading to high selectivity and reduction of side etching. Nevertheless, it has been reported that excessive or lack of a-CF x film deposition leads to various hole profile issues, such as bowing (increased hole diameter near the middle of a hole [12][13][14] ), distortion, 15,16) and striation (vertical scratches on the sidewall 17) ).…”
mentioning
confidence: 99%